AKTIVITAS ENZIM SUPEROKSIDA DISMUTASE TIKUS HIPERKOLESTEROLEMIA YANG DIBERI TEH SARAJA - Darni, Joyeti (Poltekkes Kemenkes Bengkulu, 2025)
Superoxide Dismutase (SOD) is an antioxidant enzyme that not only plays a fundamental role, but the first detoxification enzyme that plays an important role in regulating Reactive Oxygen Species (ROS) levels in the body. High SOD values ​​are associated with better health because of SOD's ability to fight oxidative stress. Corn silk is often considered as waste, it turns out to have a lipid-lowering mechanism that provides or increases the capacity of oxidative stress as well as bay leaves including very strong group antioxidant activity. The purpose of the study was to determine the activity of the superoxide dismutase enzyme in hypercholesterolemic rats given saraja tea. This study was a purely experimental study with a randomized pre-post test design with a control group design. Research on experimental animals using mice that have been made hypercholesterolemic and hypertensive, divided into 4 groups, namely the negative control group without extract administration (K-); Saraja tea intervention group (corn hair bay leaves) with extract administration of a dose of 300 mg/kg (X1); dose of 500 mg/kg (X2); and the positive group with furosemide 3.6 mg/kg (K+). The results of the study showed that the average SOD levels in group X2 with a dose of 500 mg/kg showed the highest average of 85.5 U/mL with the largest difference in SOD increase of 50.10 U/mL. The conclusion is that there is a significant difference in SOD levels between the negative control group, the positive control group, and the treatment group (X1) with a dose of 300 mg/kg, and the treatment group (X2) with a dose of 500 mg/kg.